49. THE PREVALENCE OF THYROID DISEASE IN PATIENTS WITH VITILIGO AT NATIONAL HOSPITAL OF DERMATOLOGY AND VENEREOLOGY (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the prevalence of thyroid disease in patients with vitiligo at National Hospital of Dermatology and Venereology.Materials and methods: We performed cross-sectional study on 318 patients diagnosed with vitiligo at National Hospital of Dermatology and Venereology from November 2023 to June 2024. Serum samples from patients were collected and tested for TSH, FT3, FT4, TRAb, Anti-TPO. Ultrasound was used to evaluate thyroid morphology. The patients with abnormal test results were sent to endocrinologist to confirm the diagnosis of  thyroid disease.Results: Of the 318 patients, 36 (11.3%) patients had thyroid dysfunction including  hyperthyroidism (3.4%) and hypothyroidism (7.9%). The prevalence of thyroid disease was 22%, of which autoimmune thyroid disease accounted for 8.2%, thyroid nodule accounted for 12.9% and thyroid cancer accounted for 0.9%. TRAb and Anti-TPO positivity rates were 3.1% and 17.3%.Conclusion: The study results suggested that screening for thyroid disease should be recommended in patients with vitiligo.
Keywords: Vitiligo; thyroid disease; autoimmune thyroid disease; TRAb; Anti-TPO